2015
DOI: 10.1039/c5cp01777g
|View full text |Cite
|
Sign up to set email alerts
|

Dithiafulvalene functionalized diketopyrrolopyrrole based sensitizers for efficient hydrogen production

Abstract: We have designed and synthesized two new diketopyrrolopyrrole (DPP) based organic sensitizers (DPPCA and DPPCN) with the dithiafulvalene (DTF) unit as donor and cyanoacrylic acid/malononitrile as acceptor moieties. These dyes showed excellent efficiency of photocatalytic hydrogen production over a Pt-TiO2 composite via solar-induced water splitting. The sensitizers showed broad absorptions over the wide visible regime (500-800 nm). In DPPCN, the malononitrile moiety led to strong intra-molecular charge transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Some studies concerning the use of dyes endowed with hydrophobic substituents have already been published, and in a few cases it was actually shown that elongation of the alkyl chains had a positive influence on hydrogen generation . Nevertheless, a specific investigation on the effect that different positioning of the lipophilic side chains could have on dye properties, and therefore on photocatalytic activity, was not reported so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concerning the use of dyes endowed with hydrophobic substituents have already been published, and in a few cases it was actually shown that elongation of the alkyl chains had a positive influence on hydrogen generation . Nevertheless, a specific investigation on the effect that different positioning of the lipophilic side chains could have on dye properties, and therefore on photocatalytic activity, was not reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concerningt he use of dyes endowed with hydrophobic substituents have already been published, [20][21][22][23] and in af ew cases it was actually shown that elongation of the alkyl chains had ap ositive influence on hydrogen generation. [24,25] Nevertheless,as pecific investigation on the effect that different positioning of the lipophilic side chains could have on dye properties, and therefore on photocatalytic activity,w as not reported so far.I nt his work, we decided to test a series of D-p-A dyes with hydrophobic side chains in different positions of their molecular scaffold, presuming that such designc ould influence both the reduction of dyed esorption and the anti-aggregation/recombination effect, and, at the same time, still allow SED molecules dissolved in the aqueous environment to interactwitht he oxidized dye.…”
Section: Introductionmentioning
confidence: 99%
“…[8,11] In this context, we have designed and synthesized DPP-Ful by covalent linkage of dithiafulvalene (DTF)-functionalized DPP containing oligothiophene and N-methyl fulleropyrrolidine to achieve ab road spectral response,a nd it achieved the highest PCE of 2.2 %a mong reported singlecomponent organic dyads.D PP-Ful displayed red-shifted absorption in the solid state when compared to reported fullerene-based dyads owing to strong intermolecular interactions and aggregate formation. [15,16] DPP-Ful is synthesized (Scheme 1) by refluxing C 60 -fullerene, N-methyl glycene,a nd DPP-ald [17] in toluene solvent and yields ab lue solid. [15] Thei ncorporation of DTF improves donating strength and charge transporting property,w hich is crucial to obtain high PCE.…”
mentioning
confidence: 99%
“…[15,17] Thep eak in the higher-energy region at 330 nm arises from the fullerene unit, and the peak at 380 nm arises from the oligothiophene-containing DPP unit. 330, 380, and 653 nm; absorption spectra of fullerene and DPP-ald were also recorded for comparison.…”
mentioning
confidence: 99%
See 1 more Smart Citation